Dysexecutive Syndrome in Schizophrenia: A Cross-Cultural Comparison between Japanese and British Patients - H. Ihara; G. E. Berrios; P. J. McKenna (Behavioural Neurology)
This study tested the hypothesis that the dysexecutive syndrome of schizophrenia is impervious to cultural differences. 18 Japanese and 22 British patients and 14 Japanese and 19 British control subjects were compared on the BADS (Behavioural Assessment of Dysexecutive Syndrome), a comprehensive neuropsychological assessment battery, designed for ‘ecological validity’, and other measures of frontal executive functions (EFs). Both cultural groups of schizophrenic patients showed equally severe impairment in most executive tests including the BADS (verbal fluency and intelligence were less impaired). Irrespective of cultural origin, similar neuropsychological deficits were found in patients with minimal intellectual deterioration. Our study suggests that socio-cultural background does not affect the dysexecutive profile of schizophrenia very much, and that neuropsychological assessment may possibly provide added clinical information relevant to the management and rehabilitation of schizophrenic patients across different cultures.